(3GdEjVGM aj GdefGScs - (3GdMRGej GdMhQGfj, Gdfhhj, GdTGaYqj, CHh RcQjGA, eMj GdOjf, jMj Hf TQa Hf eQj, J (B676(3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; bGd eMjj GdOjf jMji Gdfhhj GdMeO ddg Pj GdLdGd hGdEcQGg CeG HYO aEf GdML CMO CQcGf GdOjf aef Cge GdCehQ HjGf CMcGeg hEjVGM efGScg hbO LeYJ gPG GdcJGH eSJhYHG dLejY ebGUOgG s
(3BNQgG (B:s
(3hcd GdOeG JPHM aj GdMQe hjaQb GdWYGe Hg CjVG EdG aj GdEMVGQ adg Pdc MjK CMUQ hCeG GdUjGe adG jJYjf dg ecGfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B8 / 149s
(3eYLe GdeDdajf (B4 / 98s
(3cTa GdXfhf (B1 / 210s
(3TPQGJ GdPgH (B5 / 354s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdTGaYjs